2013
DOI: 10.2174/138161213805289246
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin: From Chemistry to Chemistry-Based Functions

Abstract: Curcumin is a yellow pigment found in the spice turmeric and a main functional constituent of the rhizomes of Curcuma longa. The multi-functionality of curcumin has recently attracted much attention in various fields, including food, medicinal, and clinical industries. Three major curcuminoids, curcumin, demethoxycurcumin, and bis-demethoxycurcumin, are distributed in not only Curcuma, but also the Zingiber species; however, distribution of other curcuminoids is very limited in nature. The radical scavenging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 74 publications
(77 reference statements)
0
13
0
1
Order By: Relevance
“…Curcumin, another natural polyphenol, has been the subject of investigation for its antiinflammatory, antioxidant, and antimicrobial effects. [310][311][312] Recently, the curcumin analog C66 [(2E,6E)-2,6-bis(2-(trifluoromethyl)benzylidene)cyclohexanone] was shown to be a potent antioxidant; it can prevent diabetic upregulation of JNK function, resulting in the prevention of diabetes-induced cardiac fibrosis, oxidative stress, ER stress, and cell death; it also preserves cardiac metallothionein expression. 313 The same research group demonstrated the therapeutic potential of the JNK-targeting compound C66 in treating diabetic cardiomyopathy.…”
Section: Curcuminmentioning
confidence: 99%
“…Curcumin, another natural polyphenol, has been the subject of investigation for its antiinflammatory, antioxidant, and antimicrobial effects. [310][311][312] Recently, the curcumin analog C66 [(2E,6E)-2,6-bis(2-(trifluoromethyl)benzylidene)cyclohexanone] was shown to be a potent antioxidant; it can prevent diabetic upregulation of JNK function, resulting in the prevention of diabetes-induced cardiac fibrosis, oxidative stress, ER stress, and cell death; it also preserves cardiac metallothionein expression. 313 The same research group demonstrated the therapeutic potential of the JNK-targeting compound C66 in treating diabetic cardiomyopathy.…”
Section: Curcuminmentioning
confidence: 99%
“…Presently, a growing interest for herbal medicine has prompted a large amount of scientific investigations about the biological and pharmacological properties of curcuma extract main component, curcumin, which has been shown to exert several biological actions including anti-inflammatory [ 4 - 6 ], anti-infectious [ 7 ], antioxidant [ 8 ], antithrombotic [ 9 ], antiatherosclerotic [ 10 ], anticonvulsant [ 11 ] and anticancer [ 12 - 15 ] properties, cardio [ 16 ] and neuroprotective activities [ 17 - 20 ], in addition to improving memory [ 21 ], reducing aging [ 22 ], and determining benefits in psoriasis [ 23 ]. Moreover, curcumin seems to protect from metabolic syndrome [ 24 ] decreasing insulin resistance, obesity, hypertriglyceridemia, and hypertension [ 25 ] and to prevent the complications. Curcumin, due to its antioxidant and anti-inflammatory properties [ 8 ] is therefore a multifunction phytochemical [ 26 ] that can interact with multiple molecular targets, modulating cell growth, inflammation, and apoptosis signaling pathways [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of all the health benefits of the nutraceutical value attributed to numerous different pharmacological effects (Wilken, Veena, Wang, & Srivatsan, ), there is an increasing interest toward the use of curcumin in foods and pharmaceutical formulations (Schneider, Gordon, Edwards, & Luis, ). Nonetheless, the poor solubility of curcumin in aqueous solution, its chemical instability, and low oral bioavailability have limited its integration in many food products (Anand et al., ; Fu et al., ; Jitoe‐Masuda, Fujimoto, & Masuda, ). Curcumin, moreover, has also a reduced solubility in gastrointestinal fluids and a propensity to experience chemical alterations within the gastrointestinal tract (GIT).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the poor solubility of curcumin in aqueous solution, its chemical instability, and low oral bioavailability have JFDS-2019-0755 Submitted 5/17/2019, Accepted 7/9/2019, Univ. of Molise,Via De Sanctis,Campobasso, limited its integration in many food products (Anand et al, 2007;Fu et al, 2014;Jitoe-Masuda, Fujimoto, & Masuda, 2013). Curcumin, moreover, has also a reduced solubility in gastrointestinal fluids and a propensity to experience chemical alterations within the gastrointestinal tract (GIT).…”
Section: Introductionmentioning
confidence: 99%